Potentiometric characterisation of a dual-stream electrochemical microfluidic device - Strutwolf, J.; Herzog, G.; Homsy, A.; Berduque, A.; Collins, C.; Arrigan, Damien (Springer-Verlag, 2009)
A microfluidic device is presented with offchipelectrodes residing in a reservoir and connected viamicro-capillaries to the Y-shaped microfluidic channel.The device is tested by potentiometric measurementsinvolving dual-stream laminar flow of two aqueoussolutions carrying different electrolytes at various concentrations.Open circuit potentials are measured for aseries of solutions of alkali metal chlorides and tetraalkylammoniumchlorides as well as for dilute hydrochloricacid. The open circuit potential for the microfluidic chipwas calculated by taking into account the diffusionpotential at finite ionic strength as well as the potentialdifference introduced by the reference electrode system.The liquid junction potential developed at the boundary ofthe co-flowing aqueous solutions may be manipulated tohave greater or lesser relative contributions to the measuredopen circuit potential based on use of electrolyte saltshaving cation and anion pairs of similar or dissimilarmobilities in solution. A reasonable agreement betweentheoretical and experimental values of the open circuitpotential is observed for these situations. The results showthat simple microfluidic structures possess a rich environmentfor exploration and application of the solutionchemistry of ions.